THE DESIGN APPLICATION OF ECOLOGICAL ARCHITECTURE ON INTEGRATED KAMPONG VERTICAL LIVING & URBAN VERTICAL FARMING IN YOGYAKARTA - Wiranti, Ageng; Purnomo, Agus Heru; Hardiana, Ana (Universitas Sebelas Maret Surakarta, 2019)
According to the Indonesian Central Bureau of Statistics, population growth in Yogyakarta has increased massively every year. The increased number of residents that occur, resulted in the need of house, and also the green fields will used as a residential land. Increased population definitely increase the level of food needs, but in contrast to productive land that should become a food barn of the population. Increased population will begin to shift the social side in humans because the places of interaction between individuals that should be the main forum of society to interact and socialize will be loss. Responding to this, the design application of Ecological Architecture needed, which raises a harmony between the building, human and natural environment. The research method is descriptive qualitative which begins by collecting data related to the integration of vertical living and vertical farming, literature review related to kampong vertical living theory, vertical farming system: hydroponic, and Ecological Architecture theory, then processed and concluded to be a guidance in analysis designing. From the analysis that has been done then generated an integrated design of kampong vertical living & urban vertical farming that can support sustainability design based on the application of Ecological Architecture theory.